Exciton Polaritons in Microcavities New Frontiers - Timofeev, Vladislav; Sanvitto, Daniele; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
In the past decade, there has been a burst of new and fascinating physics associated to the unique properties of two-dimensional exciton polaritons, their recent demonstration of condensation under non-equilibrium conditions and all the related quantum phenomena, which have stimulated extensive research work. This monograph summarizes the current state of the art of research on exciton polaritons in microcavities: their interactions, fast dynamics, spin-dependent phenomena, temporal and spatial coherence, condensation under non-equilibrium conditions, related collective quantum phenomena and most advanced applications. The monograph is written by the most active authors who have strongly contributed to the advances in this area. It is of great interests to both physicists approaching this subject for the first time, as well as a wide audience of experts in other disciplines who want to be updated on this fast moving field.
Future prospects of room temperature polaritons lasers -- Polariton condensation in semiconductor microcavities: similarities and differences with a photon laser -- Superfluidity of microcavity polaritons -- Bose-condensation of exciton polariton -- Exciton polaritons in organic systems -- Spin-related effects in exciton-polariton liquids -- Quantum dynamics of polariton condensates and superfluids -- Disorder effects on exciton-polariton condensates -- Nonlinear dynamics of exciton polaritons -- Exciton polariton coupling with acoustic phonons -- Stochastic classical field approach to the kinetics of a polariton condensate -- Electrically driven polariton light emitting devices -- Temporal and spatial coherence of nonequilibrium polariton condensates -- Formation and propagation of vortices in polariton OPO superfluids -- Parametric processes in microcavities and entangled polaritons pairs -- Superfuidity and coherence properties of exciton-polariton condensate.
Keywords: Physics; Microwaves; Physics; Solid State Physics; Semiconductors; Microwaves, RF and Optical Engineering; Applied and Technical Physics; Low Temperature Physics; Quantum Optics